DASAR PENAMAAN DURIAN PADA MASYARAKAT DAYAK DI DUSUN SUMIAK DESA SIDAS KABUPATEN LANDAK: KAJIAN ETNOLINGUISTIK - Laura Dinigarcia; Agus Syahrani; Mellisa Jupitasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to classify the basis of durian naming, describe the basis of durian naming, describe the function of durian naming and describe the implementation of Indonesian language learning based on the basis of durian naming in the people of Dayak Kanayatn in Sumiak Hamlet, Sidas Village, Sengah Temila District, Landak Regency. This study used descriptive methods with qualitative research forms. The source of data in this study is the people of Sumiak Hamlet. The data collection techniques in this study are interview observation techniques, talk skills, record and record. The technique of testing the validity of data in this study is observation persistence. This study resulted in 5 basic names with 33 durian names in the Dayak Kanayatn people in Sumiak Hamlet. The study resulted in six naming functions: 10 naming functions served as symbols (honor of the deceased's parents), 2 naming functions as identities, 2 naming functions as symbols (representing fauna), 1 naming function as symbols (representing flora), 2 naming functions as identifiers. The name is derived from the customary/traditional symbolization form, and 4 names serve as the symbolization form (regional boundary). The implementation of this study is a description text taught at the junior high school level, especially in class VII of the first semester.